The Effect of Lactation Education on Self-Efficacy of Breastfeeding Mothers - Nurmiaty Nurmiaty; A. Arsunan Arsin; Muh. Syafar; Aswita Aswita; Muliati Dolofu; Siti Hadijah Batjo; Rustam Aji (Poltekkes Kemenkes Palu, 2023)
Factors that affect the success of breastfeeding are the intentions for breastfeeding and the self-efficacy of the mother. Mothers with high breastfeeding intentions and self-efficacy are more likely to exclusively breastfeed in one week and four months after delivery than those with low self-efficacy. This study aims to determine the effect of lactation education on the self-efficacy of breastfeeding mothers. The study design was the quasi-experiment, pre-test, and post-test with a control group design. Samples of mothers (gestational age ≥28-32 weeks) were divided into 3 groups: 1) those who received lactation and modification modules (n = 21), 2) a group that only received modification modules (n = 21), and 3) a group that only received the maternal and child health books (n = 20). Data were collected using questionnaires, self-efficacy measurements were performed before lactation education was performed, and after 6 months of age. The result showed at initial measurement results (t0), the median self-efficacy score of respondents was between 60-79, while the median self-efficacy score of the mother at the final measurement (t1) was between 60-88. The highest score increase occurred in group 1, then group 3. The median test result showed there was a difference in self-efficacy between the three groups (p= 0,002). This finding means that lactation education with modification modules may increasing self-efficacy of breastfeeding mothers. This can be seen in group 1 which has the highest self-efficacy score and also has the highest percentage of exclusive breastfeeding percentage of all groups. Lactation education improves the self-efficacy of the mother and also increases the duration of exclusive breastfeeding. Future research can measure the mother's self-efficacy for the duration of breastfeeding.